Qualitative Geochemical Analysis of the 2004 Indian Ocean Giant Tsunami Deposits Excavated at Seungko Mulat Located in Aceh Besar of Indonesia Using Laser-Induced Breakdown Spectroscopy - Mitaphonna, Rara; Ramli, Muliadi; Ismail, Nazli; Arief, Nasrullah Idris (Indonesian Journal of Chemistry, 2024)
Laser-induced breakdown spectroscopy (LIBS) was employed to characterize the geochemical signatures layer by layer of 2004 Indian Ocean tsunami deposits in Seungko Mulat Village, Aceh Province, Indonesia. In the LIBS experimental setup, a Nd-YAG laser beam is directed towards the deposit samples, and the resulting atomic emission lines from the laser-induced plasma are captured using a spectrometer. Our analysis reveals terrestrial indicators (Fe), heavy metals (Cu, Cr, Co, Cd), and increased emission intensity of Mg, Ca, Al, K, Si, Ba, N, and O in the 2004 Indian Ocean tsunami layers. The emission intensity ratios of several elements in the 2004 Indian Ocean tsunami deposit layers, namely Ca/Ti, Si/Ti, and K/Ti, unveil notable disparities among the elements evaluated. This indicates the possibility of utilizing these ratios as reliable geochemical markers to differentiate the layer by layer of tsunami deposits. LIBS surpasses XRF in detecting nearly all elements simultaneously and identifying both light elements and specific heavy metals (Ba, Cu, Cr, Co, Cd, Pb, Ni, V, W), exceeding XRF's detection capabilities. This study emphasizes the effectiveness of LIBS as an advanced optical technique, offering speed and promise in analyzing layer-by-layer geochemical markers of the 2004 Indian Ocean tsunami deposits in Seungko Mulat Village.